Status of animal health biosecurity measures of dairy farms in urban and peri-urban areas of central Ethiopia - Moje, Nebyou; Waktole, Hika; Kassahun, Rediet; Megersa, Bekele; Chomen, Milkessa T.; Leta, Samson; Debela, Mulu; Amenu, Kebede (Frontiers in Veterinary Science, 2023)
A cross-sectional survey was carried out lasting from November 2021 to April 2022 to determine the biosecurity status of dairy farms and investigate the impact of socio-demographic characteristics on dairy farm management. Data collection was conducted through a face-to-face questionnaire survey using an online application. The interview involved a total of 380 dairy farms located in six towns in central Ethiopia. The results showed that out of the surveyed farms, 97.6% of them missed footbath at their gate point, 87.4% lacked isolation area for either sick or newly introduced cattle, and 83.4% did not check or did not quarantine newly introduced cattle. However, nearly all (97.9%) of the respondents gave medical treatments for sick cattle and 57.1% of them vaccinated their herd regularly during the past 12 months. Besides, written formal record keeping on animal health was rarely found (7.9%). On the other hand, hygienic aspects of the farms showed about 77.4% of the dairy farms appeared to clean the barn on daily basis. Yet, 53.2% of respondents did not utilize personal protective equipment during cleaning their farms. Only 25.8% of dairy farms avoided mixing their cattle with others and 32.9% implemented isolating their cattle while they were sick. In general aspects, the biosecurity assessment of the farms showed that 79.5% of dairy farms earned a score of ≤50% (‘poor’) whereas the remaining farms (20.5%) of the dairy farms received a score of >50% (‘good). Demographic characteristics of dairy farmers with biosecurity status showed a significant association with the gender of dairy farmers/owners/respondents (χ2 value = 7.61; p = 0.006), an education level (χ2 value = 12.04; p = 0.007), dairy farm ownership (χ2 value = 41.6; p < 0.001), training on dairy farm management (χ2 value = 37.1; p < 0.001), town (χ2 value = 31.69; p < 0.001), farm size (χ2 value = 7.7; p = 0.006) and herd size (χ2 value = 28.2; p < 0.001) of dairy farms. In conclusion, the level of biosecurity adoption measures among many dairy farms showed an unsatisfactory state which needs intervention in both dairy farms and public health aspects.